An Interpretation of an Affine Term Structure Model for Chile - Ochoa, J. Marcelo (Estudios de Economía, 2016)
This paper attempts to provide an economic interpretation of the factors thatdrive the movements of interest rates of bonds of different maturities in acontinuous-time no-arbitrage term structure model for Chile. The dynamics ofyields in the model are explained by two latent factors, namely the instantaneousshort rate and its time-varying central tendency. The model estimates suggestthat the short end of the yield curve is mainly driven by changes in first latentfactor, while long-term interest rates are mainly explained by the second latentfactor. Consequently, when examining movements in the term structure, oneshould think of at least two forces that hit the economy: temporary shocks thatchange short-term and medium-term interest rates by much larger amountsthan long-term interest rates, causing changes in the slope of the yield curve;and long-lived innovations which have persistent effects on the level of theyield curve.